PERSEPSI TERHADAP KEHARMONISAN KELUARGA DAN KESTABILAN EMOSI DENGAN PERILAKU AGRESIF PADA REMAJA - Rezki Yudiyasiwi, Feslika; Putu Shanti, Luh (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2023)
This research aims to examine the relationship between perceptions of family harmony and emotional stability with aggressive behavior in adolescents at SMP Negeri 2 Jatiwangi. The population of this study includes male and female students at SMP Negeri 2 Jatiwangi, with a sample size of 314 students selected using cluster random sampling. The measurement tools in this study consist of three scales: the aggressive behavior scale with a reliability coefficient of 0.927, the perception scale of family harmony with a reliability coefficient of 0.934, and the emotional stability scale with a reliability coefficient of 0.762. Data analysis techniques involve multiple regression analysis and partial correlation. The results of hypothesis testing indicate a significant negative relationship between perceptions of family harmony and emotional stability with aggressive behavior in adolescents at SMP Negeri 2 Jatiwangi, with an R value of 0.468 and an F value of 43.655, and a significance level of 0.000 (p<0.01).